ANALISIS KINERJA KEUANGAN MENGGUNAKAN LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS PADA PERUSAHAAN SUBSEKTOR KIMIA YANG TERDAFTAR DI BEI - Desi Anggraini Sitompul; Farida Khairani Lubis; Lusi Elviani Rangkuti; Heny Triastuti Kurnia Ningsih (Universitas Islam Islam Sumatera Utara, 2021)
The purpose of this study is to observe the financial condition of chemical sub-sector companies listed on the Indonesia Stock Exchange, which is viewed from the calculation of financial ratios, such as liquidity, solvency and profitability ratios. The subjects of this research are several chemical manufacturing companies, one of which is PT. Various Gas Industries, PT. Budi Starch Sweetener, PT. Madusari Murni, PT. Indo Acitama. PT. Chandra Asri Petrochemical, PT. Barito Pacific, and PT. Intan Wijaya International. While the object of this research is financial reporting which is the subject of the research, from 2017 to 2019. The data collection technique used is documentation, in the form of annual financial reporting. Analysis of the data used is descriptive analysis. The results of this study explain that the performance of the chemical sub-sector company using financial ratios, which is seen from the current ratio, quick ratio, cash ratio, debt to asset ratio, debt to equity ratio and return on equity is in poor condition. Meanwhile, the net profit margin and gross profit margin were in good condition.